PARTICULAR PATIENT QUALITY OF LIFE IN CHRONIC MIDDLE OTITIS - Агалар С. А., (World of Medicine and Biology, 2014)
Survey profiles: outpatient test of chronic otitis media (COMOT-15) questionnaire and chronic otitis (CES), conducted among 158 patients admitted to the ENT department for surgical treatment for chronic otitis media. According to the survey revealed that chronic otitis media affects the way of life, limits the choice of profession, creating many health and social problems, significantly reduces the quality of human life. Assessment of quality of life of an individual depends on the education and social status of the patient.
Keywords: сhronic otitis media; quality of life; questionnaire